Respuesta :
From the balanced equation of the reaction:
2NO2(g)↔ N2O4(g)
So we just get the Kc by using the concentration of NO2 & N2O4 and compare it with the KP value which is given.
Kc = [N2O4] / [NO2]^2
Kc = 0.084 m / 0.053^2
= 30
by comparing Kc and Kp value and we see that Kc >Kp
So the reaction will go leftward to the direction of the reactants to increase the reactants and decrease the concentration of the products until achieving the equilibrium again.
as the reaction will be at equilibrium when Kc= Kp
2NO2(g)↔ N2O4(g)
So we just get the Kc by using the concentration of NO2 & N2O4 and compare it with the KP value which is given.
Kc = [N2O4] / [NO2]^2
Kc = 0.084 m / 0.053^2
= 30
by comparing Kc and Kp value and we see that Kc >Kp
So the reaction will go leftward to the direction of the reactants to increase the reactants and decrease the concentration of the products until achieving the equilibrium again.
as the reaction will be at equilibrium when Kc= Kp
Q> K hence the reaction proceeds in the reverse direction.
First we must obtain the concentration of each of the species;
NO2 - 0.053 mol/2.35-l = 0.023 M
N2O4 - 0.084 mol/2.35-l = 0.036 M
Hence;
Q = [N204]/[NO2]^2
Q = [0.036]/[0.023]^2
Q = 68.05
Since Q > K, it follows that the reaction moves towards the left hand side.
Learn more about equilibrium: https://brainly.com/question/3930479